Foreign Language Anxiety and the Reorientation of Self-Confidence in Students Through the Fun Al-Lughawy Program - Hasyim Muzadi, Narul (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2026)
Foreign language anxiety is a significant barrier to effective language learning, often hindering students' motivation and academic performance. This study explores the perspectives of students (santri) in the Fun al-Lughawy program, aiming to assess the program’s effectiveness in reducing foreign language anxiety and enhancing self-confidence. Using a qualitative approach with a case study design, data were gathered through observations, interviews, and document analysis. The study was guided by Horwitz and Cope's Foreign Language Anxiety theory (1986), which identifies three types of anxiety: communication anxiety, test anxiety, and anxiety due to negative perceptions. The findings reveal that the Fun al-Lughawy program successfully creates a supportive and interactive learning environment, which allows students to practice foreign languages more freely and confidently. This program reduces various forms of anxiety: communication anxiety, test anxiety, and anxiety due to negative perceptions by fostering positive peer interactions and offering opportunities for practice in non-threatening settings. Ultimately, the study concludes that the Fun al-Lughawy program is effective in reducing foreign language anxiety, significantly boosting students' self-confidence, and enhancing their active participation in language learning.